Unveiling health disparities: Diagnostic prevalences in a transgender cohort versus matched controls. - Laurel Hiatt; Blessing S Ofori-Atta; Amanda V Bakian; Nicole L Mihalopoulos; Brooks R Keeshin; Anna Docherty; Michael Staley; Alison Fraser; Emily Sullivan; Erin A Kaufman; Hilary Coon; Anne V Kirby (PLoS ONE)
Importance Transgender and gender-diverse (TGD) individuals are at risk for discrimination and inequities across legal, social, and medical contexts. Population-level resources have rarely been used for TGD health research and, therefore, data is lacking about prevalences of a wide range of clinical conditions among TGD populations. Objective To leverage the Utah Population Database's demographic, vital, and health records and examine population-level diagnostic prevalences in TGD individuals and an age-matched general cohort. Participants 6,664 TGD individuals were identified using ICD codes for gender incongruence between 1995 and 2021; 64,124 age-matched individuals comprised the control cohort. Design Using Phecodes to collapse ICD codes, this study examined differences in the prevalence of medical, mental health, and neurodevelopmental clinical phenotypes in TGD and control cohorts using modified Poisson regression models. Setting Affiliated healthcare systems within the state of Utah. Main outcome and measure We evaluated adjusted prevalence ratios of identified Phecodes. Results The TGD cohort showed broadly higher documented prevalences of medical, mental health, and neurodevelopmental conditions compared to controls. Medical diagnoses more common in the TGD cohort included sleep disorders and chronic pain. Disparities in diagnoses such as "other endocrine disorders" and "need for hormone replacement therapy" likely reflect gender-affirming treatments. Mental health conditions including mood, depression, anxiety, and personality disorders were significantly more prevalent in the TGD cohort. Conclusions and relevance This study highlights diagnostic disparities for TGD individuals across multiple clinical categories. Our findings may be driven by: 1) discrimination and over-medicalization of TGD individuals, 2) differences in accessing and interacting with the healthcare system, and 3) variation in the true incidence of medical and mental health outcomes in the TGD vs control cohorts.